Preparation and Quality Assessment of Yoghurt Prepared from Dairy Milk and Coconut (Cocos nucifera, L ) Milk - Priya, S. R.; Ramaswamy, Lalitha (International Coconut Community, 2016)
Yoghurt was produced using dairy and coconut milk. Five variants of yoghurt namely plain dairy and coconut yoghurt (variant I), dairy and coconut yoghurt with natural grape pulp (variant II), dairy and coconut yoghurt with synthetic grape flavour (variant III), dairy and coconut yoghurt with natural pineapple pulp (variant IV) and dairy and coconut yoghurt with synthetic pineapple flavour (variant V) were prepared. Among these five variants dairy and coconut yoghurt with pineapple pulp (variant IV) had received the highest mean scores for all the sensory criteria, and was selected for the further study. Physicochemical properties and selected nutrient components were analysed for the pineapple flavoured yoghurt prepared with dairy milk and coconut milk. Yoghurt made with coconut milk had scored higher values for all the analysed nutrients (energy - 142.49 ± 2.63, carbohydrate - 9.55 ± 0.12, protein – 8.02 ± 0.005 and fat – 13.03 ± 0.05) than yoghurt made with dairy milk (energy - 93.76±0.25, carbohydrate - 4.46 ± 0.05 , protein – 7.26 ± 0.11 and fat – 9.82 ± 0.02). The results of current study demonstrated that the addition of fruits to the yogurt significantly improved the product acceptability and also yoghurt produced from coconut milk can be a match able substitute for normal yoghurt.